Stent fabric fatigue of grafts supported by Z-stents versus ringed stents: An in vitro buckling test. (March 2014) - Lin, Jing; Wang, Lu; Guidoin, Robert; Nutley, Mark; Song, Ge; Zhang, Ze; Du, Jia; Douville, Yvan
Stent-grafts externally fitted with a Z-shaped stents were compared to devices fitted with ringed stents in an in vitro oscillating fatigue machine at 200 cycles per minute and a pressure of 360 mmHg for scheduled durations of up to 1 week. The devices fitted with Z-stents showed a considerably lower endurance limit to buckling compared to the controls. The contact between the apexes of adjacent Z-stents resulted in significant damage to the textile scaffolds and polyester fibers due to the sharp angle of the Z-stents. The ringed stents did not cause any fraying in the textile scaffolds.